Analysis of ARV Medication Compliance in Patients With HIV/AIDS at DR. H. Kumpulan Pane Hospital, Tebing Tinggi City in 2025 - Anestetika Ginting; Ahmad Hafizullah Ritongan; Sri Melda Br. Bangun (JURNAL KESMAS DAN GIZI (JKG), 2026)
Background: HIV/AIDS remains a serious global health problem because it attacks the immune system and can progress to AIDS without regular antiretroviral (ARV) therapy. Globally, more than 37 million people are living with HIV, and Indonesia is among the countries with relatively low ARV coverage, with only around 10% of people living with HIV/AIDS (PLWHA) receiving treatment. In North Sumatra, Tebing Tinggi City is one of the areas experiencing an increase in cases; however, the utilization of HIV testing services and adherence to ARV medication remain low. A preliminary study at RSUD Dr. H. Kumpulan Pane showed that lack of information, motivation, and behavioral skills caused some patients to be inconsistent in undergoing therapy.Objective: This study aimed to analyze adherence to ARV medication among PLWHA at RSUD Dr. H. Kumpulan Pane, Tebing Tinggi City, in 2025. Methods: This study used a quantitative design with a cross-sectional approach. Results: The results showed that information, motivation, and behavioral skills had a significant effect on adherence to ARV medication among PLWHA at RSUD Dr. H. Kumpulan Pane, Tebing Tinggi City, in 2025. The better the information received, the higher the patient’s motivation, and the better the behavioral skills in managing therapy, the higher the patient’s adherence to ARV treatment. Conclusion: Information, motivation, and behavioral skills are important determinants that contribute to the success of ARV therapy among PLWHA.